134k views
4 votes
Which of the following represents another way to write the function rule f (x) = 3x + 1?

A. x = 3y + 1

B. f ( 1 ) = 4

C. f (y) = 3x + 1

D. y = 3x + 1

User Fai Ng
by
6.1k points

2 Answers

2 votes

Answer:

d

Explanation:

y=mx+b

User Staelen
by
6.0k points
0 votes

Answer:

D. y = 3x+1

Explanation:

A -- this describes the inverse function rule (x and y are interchanged).

B -- this describes one point that is described by the function rule, but does not cover the remaining infinite number of points.

C -- there is no variable y in the right side of the rule, so this would give f(1) = 3x+1, f(2) = 3x+1, and so on. The value will always be "3x+1" for any function argument. This is not the same as the given function rule.

D -- y (or any other variable except x) can stand in for f(x), so this is the same as y = f(x). It is another way to write the function rule.

User ValientProcess
by
5.4k points